Investigation of a piezo-polymer array transducer for pulse-echo ultrasonic material examinations - Tyler, N. J. (Cranfield University, 1992)
The aim of this investigation was to make a flexible array of pulse-echo ultrasound transducers by etching two orthogonal linear arrays of conducting elements into the metallisation of either side of a sheet of PVdF. These would then be multiplexed under computer control in an X-Y raster, thereby forming an image of subsurface defects in a material specimen. A potential source model was used to predict the sensitivity of a single element air-backed transducer far from resonance. Initial investigations confirmed the predictions, and reaffirmed the results of previous workers. In making a prototype array, it was found necessary to use a bi-laminar arrangement with a central ground plane, due to difficulties with crosstalk and charge leakage into the specimen materials. The radiation pattern of this array was tested and found to agree with the predictions for Fraunhofer (Far-Field) radiation. A 10 MHz analogue to digital converter was constructed to interface with the IBM-PC clone as a transient recorder, through a data capture program written in 'C'. However, the electrical noise generated by the PC was found to interfere strongly with the signal from the array transducer. A wide-band amplifier and full-wave rectifier was then added to the multiplexer and A/D converter, and the system enclosed in an electrically isolated environment, which made it possible to obtain clear signal data from the transducer. Non-linear regression was implemented in the software, to smooth the data and locate echo peaks, and the most frequently occurring peak separation was used to indicate sample thickness at that location in a false-colour mapping on the screen of the PC.